A Meta-analysis: Trends in the use of augmented reality in biology learning (2016-2025) - Setiawan, Erik; Darmawan, Ericka; Alamsyah, Muhammad Radian Nur (Biosfer: Jurnal Pendidikan Biologi, 2025)
Augmented reality, which can visualize abstract concept especially in biology education has made these concepts more tangible, engaging, and easier to understand in biology education. This study employs a mixed-method meta-analysis approach (qualitative and quantitative) to examine the trends in the use of augmented reality in biology education from 2016 to 2025. A total of 35 articles were selected from 100 reviewed, based on inclusion criteria guided by the PRISMA protocol. The qualitative analysis was conducted by examining the thematic trends of the articles, while the quantitative analysis was carried out through effect size calculations. Research and Development (37%) and quasi-experiments (34%). The studies were predominantly conducted in the Java region, particularly West Java and East Java, indicating that there is still a technological gap between regions in Indonesia. The most frequently studied variables included concept understanding and learning outcomes (each with 7 articles) and learning motivation (6 articles). Quantitative analysis of 6 articles showed an average effect size of 2.249, which falls into the very high category.